Co-benefits and trade-offs of environmental pressures: A case study of Zhejiang's socio-economic evolution. (10th May 2020) - Zhang, Shuo; Wang, Dong; Hong, Liyun; Ren, Hongtao; Feng, Cuiyang; Liang, Yuhan; Kharrazi, Ali; Yu, Yadong; Liang, Sai
Abstract: Our societies are continuously grappling with how to achieve rapid economic growth while minimizing the challenges of environmental sustainability. In this avenue, numerous studies have contributed towards investigating socio-economic factors and developing policies targeting environmental pressures (EPs). While previous studies have tended to focus on the individual driving forces of EPs, the consideration of the co-benefits and trade-offs among different EPs and policies have been considerably overlooked. In China, previous studies have mostly engaged these issues at the national level and have overlooked the regional socio-economic characteristics – this presents a mismatch between regional policy applications and average national level research findings. Towards this end, this study examines the co-benefits and trade-offs of eight EPs in Zhejiang during the 2007–2015 period. Our findings revealed strict co-benefits in reductions of all eight EPs due to intensity changes as well as trade-offs due to changes in final demand structure and final demand composition. Sectoral results show that only the Non-Ferrous Metal Ores sector has strict co-benefits among all EPs from the production perspective, while eight sectors have strict co-benefits from the consumption perspective mainly including the Mining and Washing of Coal, Ferrous Metal Ores, Electric Power and Heat Power sectors. Our findings suggest important policy implications associated with utilizing co-benefits and avoiding trade-offs for EP mitigation: making full use of all driving forces, strengthening intersectoral coordination, and establishing a joint evaluation mechanism among different sectors. Graphical abstract: Image 1 Highlights: Environmental pressures (EPs) in Zhejiang's socio-economic evolution were studied. Sectorial level co-benefits and trade-offs of eight EPs in Zheijiang were analyzed. Strict co-benefits in reducing EPs were observed through intensity changes. EPs had more trade-offs than co-benefits at the sectorial level. Mitigation of EPs demand utilization of co-benefits and avoidance of trade-offs.